A novel efficient polymeric flame retardant for poly (lactic acid) (PLA): Synthesis and its effects on flame retardancy and crystallization of PLA. (October 2015) - Liao, Fenghui; Ju, Yaqing; Dai, Xiu; Cao, Yu; Li, Jiawei; Wang, Xinlong
Abstract: A novel polymeric flame retardant (PNFR) containing phosphorus, ester groups and phenyl rings on the backbone was synthesized and analyzed by 1 H NMR, FTIR, DSC, XRD and GPC. The crystallization of the poly (lactic acid) (PLA) composites with different content of PNFR was studied by DSC. The flame retardancy of the PLA composites with PNFR was investigated by limited oxygen index (LOI), cone calorimetry and vertical burning tests (UL-94). The results indicated that low loading of PNFR could significantly improve flame retardancy and crystallinity of PLA. The LOI was increased to 31.5 vol%O2 and UL-94 V-0 was attained for the PLA composites with loading of 3 wt% PNFR. Moreover, the crystallinity of this sample reached 46.03%. The char residues after the burning of the PLA composites with PNFR were analyzed by SEM, XRD, Raman and XPS.